Estudo in vivo e in vitro da citotoxicidade e das propriedades físico-químicas de resinas compostas experimentais para capeamento pulpar direto - Silva, Julianne Coelho da (2018)
The aim was to investigate the physicochemical properties of experimental composite resins with bioactive particles and to evaluate cytotoxicity and in vivo pulp response to direct pulp capping. The experimental resins were prepared and, subsequently, the hydroxyapatite nanoparticles adsorbed with simvastatin and glutathione were added at 0% (Control Resin), 1% (Res 1%) and 10% (Res 10%) by weight. Photopolymerizable calcium hydroxide [Ca(OH)2] (Ultra-blend Plus, Ultradent) was used as the control group. The physicochemical properties studied were flexural strength and elastic modulus through three-point bending test (n = 10), calcium release (n=6) and degree of conversion (n=3) assessed by spectroscopy Raman. Proliferation and cell counting assays were performed to evaluate in vitro cytotoxicity and the cells were observed in confocal microscopy with live/dead dyes. To evaluate the pulp response, pulp capping was performed directly on the lower molars of Wistar rats (n=6). The animals were euthanized after 7 days of the procedure, and the hemimandibules removed for the preparation of slides and histological analysis. Statistical analysis was performed with Kruskall-Wallis and ANOVA with Tukey post-test. The level of significance was 5%. In flexural strength there was no statistical difference between groups (p> 0.05). In the elastic modulus, Res 10% presented the best results, but revealed no statistical difference with Res 1%, which did not differ statistically from the further groups. In the degree of conversion, the results of the Res 10% were statistically higher than the resins 0% and 1%. Ca(OH)2 showed higher calcium release after 28 and 45 days of storage, with no statistical difference in the second period with the Res 10% group. No significant statistical difference was observed in the cell proliferation assay. By the confocal microscopy analysis, the resins at lower concentrations showed higher cell viability. In the evaluation of the pulp response, it was possible to observe pulp damage in the group treated with calcium hydroxide. Therefore, it can be concluded that the experimental resin may be a viable alternative to Ultra-blend Plus calcium hydroxide; however, further studies are necessary to prove the repair of pulp tissue and dentin neoformation.